Pengaruh Lingkungan Teman Sebaya Terhadap Perilaku Ekonomi Siswa SMK Palapa Bandar Lampung - Rini, Emilia Astika; Indriani, Meita; Simarmata, Aisyah Maharani; Romansa, Nikolaus; Berliana, Berliana; Rahmawati, Rahmawati; Pritandhari, Meyta (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the extent to which peer environment influences the economic behavior of 11th-grade students in the Accounting and Financial Institution program at SMK Palapa Bandar Lampung. The research uses a quantitative approach with a survey and ex post facto method. A total of 30 students were selected using a saturated sampling technique. Data were collected through a closed-ended questionnaire using a semantic differential scale. The instrument was tested for validity and reliability (α = 0.814). Classical assumption tests included normality, multicollinearity, autocorrelation, and heteroscedasticity. Hypothesis testing was conducted using simple linear regression with the model Y = α + βX + e, along with a t-test and coefficient of determination. The results show that the peer environment has a positive and significant influence on students' economic behavior, indicated by a t-value of 4.625 > t-table value of 2.056 and a significance level of 0.000 < 0.05. The regression coefficient of 0.937 indicates a positive direction of influence, and the adjusted R² value of 0.413 means that 41.3% of economic behavior is explained by peer interaction. These findings suggest that associating with peers who practice responsible economic habits encourages students to manage their finances more wisely and rationally.